2022
DOI: 10.3389/fneur.2022.792695
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Asymmetry in Precentral and Postcentral Gyrus in Patients With Unilateral Chronic Shoulder Pain

Abstract: ObjectiveThe purpose of this study was to explore the structural and functional asymmetry of precentral and postcentral gyrus in patients with unilateral chronic shoulder pain (CSP) utilizing MRI.Patients and MethodsWe collected structural and resting-state functional MRI (rs-fMRI) data in 22 left-sided, 15 patients with right-sided CSP, and 24 healthy controls (HCs). Here, we performed the structural asymmetry and seed-based functional connectivity (FC) analyses. We extracted regional cortical thickness and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The postcentral gyrus is an important component of the primary somatosensory cortex that is involved in pain and sensory information processing and is responsible for encoding pain sensation information. 20,21 As a region located in the medial prefrontal cortex of the brain, the sgACC plays a crucial role in the descending pain modulation system and has been shown to participate in the processing and perception of pain-related information in patients with CBP. [22][23][24] Therefore, the central posterior gyrus and sgACC play an important role in the processing of pain information.…”
Section: Discussionmentioning
confidence: 99%
“…The postcentral gyrus is an important component of the primary somatosensory cortex that is involved in pain and sensory information processing and is responsible for encoding pain sensation information. 20,21 As a region located in the medial prefrontal cortex of the brain, the sgACC plays a crucial role in the descending pain modulation system and has been shown to participate in the processing and perception of pain-related information in patients with CBP. [22][23][24] Therefore, the central posterior gyrus and sgACC play an important role in the processing of pain information.…”
Section: Discussionmentioning
confidence: 99%
“…For example, morphologic properties of the anterior cingulate, frontal, and temporal cortices are strongly associated with the clinical presentation of people with CNNP. 15 Increased volume of the postcentral gyrus (location of the primary somatosensory cortex) has been associated with increased levels of pain, 49 and increased amygdala and decreased cingulate volume have been associated with increased levels of anxiety and depression in people with chronic pain. 50,51 Being able to alter those volumetric properties through exercise therapy might demonstrate that clinical improvements are associated with positive structural changes in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The PrCG belongs to the "pain matrix", which is closely related to aversive experiences we call "pain" (Garcia-Larrea and Bastuji, 2018; Tang et al, 2021). An increasing body of evidence suggests that the PrCG exhibits brain functional and structural reorganization in many pain-related diseases, such as shoulder pain, neck pain, migraine, or facial pain (Cunningham et al, 2015;Niddam et al, 2019;Wei et al, 2022;Yue and Du, 2020). A systematic review revealed that the PHN was closely associated with structural and functional abnormalities of the PrCG (Tang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%